Intravenous single administration of amiodarone and breastfeeding. (4th January 2019) - Javot, Lucie; Pape, Elise; Yéléhé‐Okouma, Mélissa; Barotte, Emilie; Divoux, Emmanuelle; Gillet, Pierre; Gambier, Nicolas; Scala‐Bertola, Julien
Abstract: Amiodarone treatment is contraindicated during breastfeeding. As the regional pharmacovigilance centre, we were contacted for information relative to the possibility of breastfeeding after single intravenous administration of 450 mg amiodarone to a breastfeeding woman. A monitoring of amiodarone concentration in plasma and milk was performed in the mother. At day 4, milk concentration of amiodarone reached a peak (233 μg/L) and milk to plasma ratio was determined to 3.5. Milk concentration was still detectable at day 10 (132 μg/L). The maximal relative infant dose was estimated to be 0.6% of the maternal weight‐adjusted dosage, corresponding to 0.18% of the usual posology used in children by parenteral route. The review of the literature retrieved one publication suggesting that a single intravenous administration of 150 mg of amiodarone to a mother represents a negligible infant risk based on low breast milk concentration. The French National Pharmacovigilance database query did not disclose any case of side effects during breastfeeding after a single dose of amiodarone. A very limited exposition of breastfed newborns to amiodarone, as well as a low risk of side effects, is expected after a single administration of amiodarone to their mothers.